Unpacking Student Engagement in Gamified English Learning: Teachers’ Perspectives on the Pedagogical Use of Kahoot - Khoirotul Juniper; Syaiful Islam (CV. Doki Course and Training, 2026)
Student engagement has become a critical factor in achieving successful English language learning outcomes, particularly in technology-enhanced learning environments. Among various gamified learning platforms, Kahoot has gained increasing attention for its potential to promote active participation and classroom interaction. However, studies exploring teachers’ lived experiences in using Kahoot to support student engagement remain limited. Therefore, this study aimed to explore teachers’ perspectives and experiences regarding the pedagogical use of Kahoot in English language learning This study employed a qualitative method using a phenomenological design. Two English teachers from Bhakti Pertiwi Junior High School were purposively selected as participants based on their experience in implementing Kahoot in English classrooms. Data were collected through semi-structured interviews and classroom observations and analysed using Miles and Huberman’s interactive model, including data collection, data reduction, data display, and conclusion drawing and verification. The findings revealed three major themes. First, teachers experienced Kahoot as a tool that created an enjoyable learning atmosphere and fostered classroom interaction. Second, Kahoot contributed positively to students’ behavioral, emotional, and cognitive engagement by increasing participation, motivation, enthusiasm, and attention to learning content. Third, teachers encountered several challenges, including unstable internet connectivity, limited access to digital devices, and classroom management issues during game-based activities. The study concludes that Kahoot is an effective gamified learning platform for enhancing student engagement in English language learning. The findings provide practical insights for teachers and contribute to the growing literature on gamification, student engagement, and technology-enhanced language learning